2012
DOI: 10.1590/s0100-67622012000100003
|View full text |Cite
|
Sign up to set email alerts
|

Época de coleta e ácido indolbutírico no enraizamento de estacas de espirradeira (Nerium oleander L.)

Abstract: -Nerium oleander plants are important ornamental trees, much cultivated in urban centers

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
2
1
10

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 9 publications
4
2
1
10
Order By: Relevance
“…The most appropriate time for picking was during the summer, but not differing from the spring collection, similar from the previous study Contrary to the result found, Pivetta et al [13] observed that rooting of Ne- Stuepp et al [14] studying IBA effect on Ilex paraguariensis demonstrated that autumn is the most enabling season for cuttings rooting, followed by spring and winter.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The most appropriate time for picking was during the summer, but not differing from the spring collection, similar from the previous study Contrary to the result found, Pivetta et al [13] observed that rooting of Ne- Stuepp et al [14] studying IBA effect on Ilex paraguariensis demonstrated that autumn is the most enabling season for cuttings rooting, followed by spring and winter.…”
Section: Resultssupporting
confidence: 81%
“…Pivetta et al [13] still observed that the number and length of roots was higher in the winter period for Nerium oleander for pink flowers, however, the dry mass of roots was higher in the winter. ) and: (a) average root length in cm in winter and (b) root dry mass, in g, in winter for "Fine Time" chrysanthemum cuttings.…”
Section: Resultsmentioning
confidence: 96%
“…Alguns estudos demonstram outras variáveis afetando enraizamento adventício tais como substrato (MENDES et al, 2014;COSTA et al, 2015;HUSSAIN et al, 2014;CARDOSO et al, 2011;PELIZZA et al, 2011), forma de aplicação de reguladores vegetais (PEÑA et al, 2012), aditivos como a sacarose (LAMEIRA et al, 1997), época de coleta de material propagativo (PIVETTA et al, 2012;LIMA et al, 2011b;PIZZATTO et al, 2011), características anatômicas dos tecidos vegetais (LIMA et al, 2011a) de AIB e que concentrações acima de 1.000 mg L -1 não estimularam a formação de raízes (ALCANTARA et al, 2010).…”
Section: Resultados E Discussõesunclassified
“…Resultados obtidos neste experimento assemelham-se aos observados por outros autores, quando da utilização de reguladores de crescimento para enraizamento de estacas, quando comparados ao tratamento testemunha, ou seja, sem a utilização de indutores. PIVETTA et al (2012) também citam que para se obter estacas enraizadas, em qualquer época do ano, deve-se lançar mão de auxinas sintéticas na promoção do enraizamento.…”
Section: Figuraunclassified